2020
DOI: 10.1002/ajh.25910
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding phenotype and diagnostic characterization of patients with congenital platelet defects

Abstract: Phenotypic characterization of congenital platelet defects (CPDs) could help physicians recognize CPD subtypes and can inform on prognostic implications. We report the analyses of the bleeding phenotype and diagnostic characteristics of a large cohort of adult patients with a confirmed CPD. A total of 96 patients were analyzed and they were classified as Glanzmann thrombasthenia, Bernard‐Soulier syndrome, dense granule deficiency, defects in the ADP or thromboxane A2 (TxA2) pathway, isolated thrombocytopenia o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
(12 reference statements)
1
15
0
Order By: Relevance
“…The RBiN study was performed between 2017 and 2019 and included 263 patients with RBDs [15] . The TiN study was performed between 2016 and 2018 and included 62 patients with confirmed CPDs [16] . These three studies included patients from all Hemophilia Treatment Centers in the Netherlands.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The RBiN study was performed between 2017 and 2019 and included 263 patients with RBDs [15] . The TiN study was performed between 2016 and 2018 and included 62 patients with confirmed CPDs [16] . These three studies included patients from all Hemophilia Treatment Centers in the Netherlands.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with hyperfibrinolysis were eligible if the euglobulin clot lysis ratio before and after application of a tourniquet was ≥5.8 (reference range 1.2–5.7, locally validated assay). From the TiN study, we included patients with a confirmed CPD: Bernard Soulier Syndrome, Glanzmann thrombasthenia, Adenosine diphosphate (ADP) pathway defect, Thromboxane A2 (TxA2) pathway defect and dense granule deficiency [16] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SYMPHONY provides the opportunity to expand to prospective clinical trials 12 to achieve population PK‐PD models that will finally associate coagulation factor levels with bleeding events, which is urgently needed, and additionally to develop a user‐friendly PK‐PD tool 32 Other clinical multicenter studies in bleeding disorders initiated in the Netherlands: Hemophilia in the Netherlands (HiN); von Willebrand in the Netherlands (WiN); Thrombocytopathy in the Netherlands (TiN); Rare Bleeding Disorders in the Netherlands (RBiN); studies into bleeding of unknown cause (CRESCENDO); international studies initiated in the Netherlands, including INSIGHT/RISE/DYNAMO 1,13–15,17,18,29 . All studies provide interesting patient material to deepen our understanding of interindividual differences.…”
Section: Methodsmentioning
confidence: 99%
“…results from earlier multicenter (inter)national studies in which clinical data and blood samples have been collected, 1,[12][13][14][15][16][17]29 expanding and linking these to fundamental research on the biochemistry of hemostasis, molecular genetics, proteomics, and cellular disease models.…”
Section: An Integrated Interdisciplinary Research Programmentioning
confidence: 99%